THE NEEDS ANALYSIS OF BLENDED LEARNING IPA TERPADU - Iman Nasrulloh; Nurdin Ibrahim; Etin Solihatin (Green Publisher, 2022)
The impact of technological advances in education has offered forms of ICT-based learning approaches that require teachers to continue to innovate to improve the quality of education. Learning innovations should continue to be carried out by teachers as educators to answer the need to overcome learning problems. This study aims to analyze the factors needed for blended learning and provide recommendations regarding the factors in the design and development of Integrated Science blended learning. Characteristics of students and teacher experience become input in designing blended learning. Recommended factors for integrating Integrated Science blended learning to include technological infrastructure, pedagogical models, and learning strategies.